Objective Evaluation of Oral and Pharyngeal Areas in Autopsy Cases of Obstructive Sleep Apnea Syndrome via Postmortem CT - Takeuchi, Akiko; Hyodoh, Hideki; Jin, Shigeki; Tanaka, Satoshi; Murakami, Manabu; Minowa, Kazuyuki; Matoba, Kotaro (Current Medical Imaging, 2024)
Background Obstructive sleep apnea syndrome (OSAS) can cause sudden death during sleep. Previous findings have suggested that OSAS development is related to maxillofacial morphology. Evaluation of facial morphology can determine the risk of developing the disease, and establishing an objective method to assess the underlying etiology of OSAS-related death would be advantageous. Objective The objective of this study is to determine the key features of obstructive sleep apnea syndrome (OSAS) using postmortem oral and pharyngeal computed tomography (CT). Methods We retrospectively assessed autopsy cases of patients with (n=25) and without (n=25) OSAS-related death. We used oral and pharyngeal CT images to compare the oral and pharyngeal cavity volume (OPCV), oral and pharyngeal soft tissue volume (OPSV), oral and pharyngeal air space volume (OPAV), and OPAV to OPCV ratio (%air). Receiver operating curve (ROC) analysis was used to determine the accuracy of OSAS prediction. We assessed participants with body mass index (BMI) values within the normal range. Results Among the 50 subjects, we observed significant between-group differences in OPSV, OPAV, and % air, whereas there were significant between-group differences in OPSV and %air among 28 subjects with normal BMI values. Both comparisons suggested that OSAS-related death was associated with low %air and high OPSV values. Conclusion The % air and OPSV are useful for assessing postmortem oropharyngeal CT images. OSAS-related sudden death is likely when %air and OPSV values are ≤20.1% and ≥127.2 ml, respectively. Among those with normal BMI values, % air and OPSV values of ≤22.8% and ≥111.5 ml, respectively, predict OSAS-related sudden death.
Keywords: Three-dimensional computed tomography